Inflammatory bowel disease caused by primary immunodeficiencies—Clinical presentations, review of literature, and proposal of a rational diagnostic algorithm. Issue 5 (1st August 2017) - Tegtmeyer, Daniel; Seidl, Maximilian; Gerner, Patrick; Baumann, Ulrich; Klemann, Christian
Abstract: Inflammatory bowel diseases (IBD) including Crohn's disease (CD) and ulcerative colitis have a multifactorial pathogenesis with complex interactions between polygenetic predispositions and environmental factors. However, IBD can also be caused by monogenic diseases, such as primary immunodeficiencies (PID). Recently, an increasing number of these altogether rare diseases have been described to present often primarily, or solely, as IBD. Early recognition of these conditions enables adaption of therapies and thus directly benefits the course of IBDs. Here, we discuss the different clinical presentations in IBD and characteristic features of patient's history, clinical findings, and diagnostic results indicative for a causative PID. Possible predictors are early onset of disease, necessity of parenteral nutrition, failure to respond to standard immunosuppressive therapy, parental consanguinity, increased susceptibility for infections, certain histopathologic findings, and blood tests that are atypical for classic IBD. We illustrate this with exemplary case studies of IBD due to NEMO deficiency, chronic granulomatous disease, common variable immunodeficiency, CTLA‐4 and LRBA deficiency. Taking these factors into account, we propose a diagnostic pathway to enable early diagnosis of IBD due to PID. Abstract :